On Joint Sub-channel Allocation, Duplexing Mode Selection, and Power Control in Full-Duplex Co-Channel Femtocell Networks - M. Rasti; Sh. Kazemi Taskou (AUT Journal of Electrical Engineering)
As one of the promising approaches to increase the network capacity, Full-duplex (FD) communications have recently gained a remarkable attention. FD communication enables wireless nodes to simultaneously send and receive data through the same frequency band. Thanks to the recent achievements in the self-interference (SI) cancellation, this type of communication is expected to be potentially utilized in cellular systems, especially in small cell networks. In this paper, we integrate the FD communications into femtocell networks where femtocell users (FUs) share the same spectrum with macro users (MUs). In particular, aiming to maximize the number of admitted FUs in the network and satisfying the target rate for FUs, we jointly study the problem of sub-channel allocation, duplexing-mode selection, and power control for FUs in both uplink (UL) and downlink (DL) transmissions. Moreover, we address the power control problem for macro-tier where the main goal is to minimize the transmission power of prioritized MUs while guaranteeing a target rate for them. To jointly address these problems for both tiers, we propose a distributed algorithm in which FBSs and admitted FUs choose whether to operate in half-duplex (HD) or FD mode so as to meet their target rate. The convergence and performance of the proposed algorithm are evaluated through simulation where it is demonstrated that the average admission ratio of FUs in our proposed distributed scheme surpasses the existing traditional HD approaches.